Multipoint Problem with Multiple Nodes for Partial Differential Equations - Ptashnik, B. I.; Symotyuk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish conditions for the existence and uniqueness of a solution of a problem with multipoint conditions with respect to a selected variable t (in the case of multiple nodes) and periodic conditions with respect to x 1,..., x p for a nonisotropic partial differential equation with constant complex coefficients. We prove metric theorems on lower bounds for small denominators appearing in the course of the solution of this problem.